The Use of Translanguaging by Students of the English Education Study Program in Class Discussion at Universitas Muhammadiyah bengkulu - Erza Kurnia Zahari; Yupika Maryansyah; Dian Susyla; Epi Wadison (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Translanguaging, the strategic use of multiple languages within communication, has emerged as a significant pedagogical phenomenon in multilingual classrooms. In English as a Foreign Language (EFL) contexts, it enables students to draw on their full linguistic repertoire to enhance comprehension and participation. This study examines the types and functions of translanguaging employed by students during class discussions in the Second Language Acquisition (SLA) course at the English Education Study Program, UniversitasMuhammadiyah Bengkulu. This study employed a descriptive qualitative design, data were gathered through video recordings of three discussion sessions, transcriptions, and structured observations based on the classifications of Hoffman (1991) and Poplack (1980). The analysis identified three main types: intra-sentential, inter-sentential, and tag translanguaging, with intra-sentential being the most prevalent, often used to embed technical terms within Indonesian explanations. Functions observed include clarifying academic concepts, providing culturally relevant examples, and fostering inclusive social interaction. These findings indicate that translanguaging in EFL classroom discussions operates as a deliberate and strategic communication approach rather than random language mixing. It can serve as an effective pedagogical tool to improve comprehension and active engagement, suggesting its potential for broader application in EFL learning environments. Keywords: Classroom Discussion, EFL Students, Second Language Acquisition (SLA), Translanguaging.